Clinical, hormonal, radiological and morphological comparison of patients with clinically evident Cushing's disease and patients with silent corticotroph cell adenoma - Gamze Akkuş; Baris Karagün; Nuri Eralp Çetinalp; Arbil Açıkalın; Fulya Odabaş; Mehtap Evran Olgun; Murat Sert; Suzan Zorludemir; Bekir Tamer Tetiker (Cukurova Medical Journal, 2020)
Purpose: The aim of the study was to review our clinical 7 years experiences with silent corticotroph adenoma (SCA) and Cushing disease (CD) with regard to clinical, radiological features, immunohistochemical and surgical outcomes and compare the results between two groups. Material and Methods: We retrospectively reviewed a series of patients (n=17; SCA 10, CD 7) with corticotroph adenomas and collected biochemical, neuroradiological and pathological data of those during follow-up time. Results: Mean pre-operative ACTH values of the patients with CD and SCA were 60.4±29.5, 45.5±34.6 pg/mL, respectively. Mean preoperative cortisol of the patient with CD (21.2±4.4 vs 11.5±4.0 mcg/dL) was increased than the patients with SCA measurements’. Patients with SCA had larger pituitary mass (20.4±4.5 vs 8.8±4.0 mm) than the patients with CD. And cavernous sinus invasion also was determined in all patients with SCA. Sparsely granulation staining was more common in all patients with SCA (7/10) or CD (4/7). Conclusion: SCAs are totally different from functional CD adenomas related with clinical characteristics and postoperative outcomes. SCA can be thought of as a diverse group of pituitary adenomas.